Transesterfication Process of Waste Cooking Oil Catalyzed by Na/CaO Derived from Blood Clam (Anadara Granosa) Shells - Edi Kurniawan; Nurhayati Nurhayati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Abstract: Blood clam (Anadara granosa) shells has the potential to be developed as a base heterogeneous catalysts for biodiesel production. Blood clam (Anadara granosa) shells has a high mineral content of calcium carbonate (CaCO3). CaCO3 can be decomposed into CaO at high temperature heating. In this study, CaO catalyst synthesized from the blood clam (Anadara granosa) shells calcined of 900 °C for 10 hours and then impregnated using NaOH (1, 3, and 5% w/w) the activation temperature of 600 °C for 5 hours. 3% Na/CaO catalyst was the most better catalyst with maximum biodiesel results obtained at 83,57% using the 3% Na/CaO catalyst. The maximum conditions obtained from biodiesel production using the 3% Na/CaO catalyst on the reaction temperature at 60 °C, the reaction time of 3.5 hours, stirring speed of 250 rpm, 3 g weight of catalyst, and the mole ratio of oil: methanol 1: 6.Keywords: Biodiesel, Transesterification, Blood clam shells, Heterogeneous base catalystReceived: 29 September 2019; Accepted: 2 December 2019; Published: 15 January 2020